Book Launch of Political Economy and Policy Analysis (PEPA) Sourcebook Video - CGIAR (CGIAR System Organization, 2023)
This video was recorded last October 10, 2023 at the book launch of the Political Economy and Policy Analysis (PEPA) Sourcebook. Stakeholders working in food system policy research and development often ask, “What works where, why, and how?” These fundamental questions fuel other important debates—what are the “windows of opportunity” for reform and policy change? Are biotech crops part of the solution to solving climate, food, and nutrition security challenges in developing economies? What institutional innovations are “best fit” for managing shared natural resources to avoid conflict?